Model for MHD Flow of Casson Nanofluid Over A Stretching Sheet With Newtonian Heating and Thermal Radiation Effects - Kho, Yap Bing; Abid, Hussanan; Norhafizah, Md Sarif; Zulkhibri, Ismail; Mohd Zuki, Salleh (2017)
The boundary layer and heat transfer flow of Casson nanofluid past over a stretching sheet with Newtonian heating have been studied numerically. The effect of magnetic field and thermal radiation have been examined well. Subjected to the similarity transformations, the governing equations are then reduced to non-linear ordinary differential equations. The effects of non-Newtonian Casson parameter, radiation parameter, magnetic parameter, Prandtl number, Brownian motion parameter, Schmidt number and thermophoresis parameter on temperature, concentration and velocity fields are shown graphically and discussed. In order to get physically appropriate solutions, the numerically solutions for non-Newtonian parameter have been carried out with the asymptotic boundary conditions.